Access to justicie for children and adolescents - Bello Janeiro, Domingo (2021)
Children are vulnerable group with special difficulties protection for which the frst thing is that children are more aware of their rights to be heard and heard, especially in cases of gender-based violence, with special care in their access to justice in relation to the legal prohibition of joint custody and custody of minor children, as well as in the suspension of the joint custody measure agreed in the judgment, being It is necessary to provide psychological care after legal proceedings against victims of gender violence, as well as to prevent digital gender violence among young people and provide comprehensive protection regulations for children, especially against the scourge of violence.